The Tryptophan Pathway Targeting Antioxidant Capacity in the Placenta. (22nd July 2018) - Xu, Kang; Liu, Gang; Fu, Chenxing
Abstract : The placenta plays a vital role in fetal development during pregnancy. Dysfunction of the placenta can be caused by oxidative stress and can lead to abnormal fetal development. Preventing oxidative stress of the placenta is thus an important measure to ensure positive birth outcomes. Research shows that tryptophan and its metabolites can efficiently clean free radicals (including the reactive oxygen species and activated chlorine). Consequently, tryptophan and its metabolites are suggested to act as potent antioxidants in the placenta. However, the mechanism of these antioxidant properties in the placenta is still unknown. In this review, we summarize research on the antioxidant properties of tryptophan, tryptophan metabolites, and metabolic enzymes. Two predicted mechanisms of tryptophan's antioxidant properties are discussed. (1) Tryptophan could activate the phosphorylation of p62 after the activation of mTORC1; phosphorylated p62 then uncouples the interaction between Nrf2 and Keap1, and activated Nrf2 enters the nucleus to induce expressions of antioxidant proteins, thus improving cellular antioxidation. (2) 3-Hydroxyanthranilic acid, a tryptophan kynurenine pathway metabolite, changes conformation of Keap1, inducing the dissociation of Nrf2 and Keap1, activating Nrf2 to enter the nucleus and induce expressions of antioxidant proteins (such as HO-1), thereby enhancing cellular antioxidant capacity. These mechanisms may enrich the theory of how to apply tryptophan as an antioxidant during pregnancy, providing technical support for its use in regulating the pregnancy's redox status and enriching our understanding of amino acids' nutritional value.